Aspectos da ecologia trófica e distribuição vertical de uma população de Dendropsophus gr. Microcephalus (Anura, Hylidae) em uma area de mata de tabuleiro litorâneo do Nordeste brasileiro - Gondim, Patrícia de Menezes (2012)
In this work, it was studied the diet and vertical stratification in D. gr. microcephalus in an area of coastal tableland of northeastern Brazil. Regarding diet, it was identified the main food items, the occurrence of sexual, ontogenetic and seasonal variation in relation to the consumed prey, as well as the ratio of length and volume of these with the snout-vent length and jaw width. As for the vertical stratification, it was analyzed possible sex, ontogenetic and seasonal time differences for perch height. The field work took place monthly from March to December 2011, totalizing ten months of collections, obtaining a sample of 229 individuals (177 males, 52 females). It was quantified 464 prey distributed in 15 categories, being Diptera, Coleoptera, Araneae e Hemiptera the main items consumed,food composition found in most species of the genus. The predominance of Diptera in dietary composition points out Dendropsophus as an important group of biocontrol of harmful insects. Females had higher values than males in relation to snout-vent length (SVL), jaw width (JW) and body mass, being jaw width the responsible for the sexual and ontogenetic differences when related to length and volume of items consumed. With regard to seasonal variation, length and volume of food items were greater during the rainy season, suggesting a greater abundance of prey during this period. The height of perch D. gr. microcephalus was similar to that found in other species of the genus. Adults perched at lower altitudes, while youngsters have reached greater heights, differences that are related to the jaw width and possibly to the SVL and body mass. Vertical stratification due to seasonal variations may be linked to abiotic factors such as temperature, relative humidity and / or wind; however, further studies should be conducted to confirm the relationship of these factors, not only with seasonal variations, but also with sexual and ontogenetic variations.